PENGARUH MODAL TERHADAP PENDAPATAN PEDAGANG PASAR SANGATTA SELATAN KABUPATEN KUTAI TIMUR - Nermala Nermala; Nuuridha Matiin; Angga Kusumah (Tinta Nusantara 2018 Vol.1, 2022)
The purpose of this study was to determine how the effect of capital on the income of South Sangatta market traders. To apply these objectives, a descriptive method is used with the help of the SPSS version 20 program with the formulas, namely simple regression analysis, t test and r test. And the sample in this study were 67 traders. The hypothesis which states that working capital has a significant effect on the level of income is accepted. After calculating the value of the determinant coefficient (R2) of 0.162 or 16.2%. This means that the capital variable on income contributes quite effectively while the remaining 83.8% is influenced by other variables.